GRIK phosphorylates and activates KIN10 which also promotes its degradation - Sun, Jing; Liu, Hui; Blanford, Jantana K.; Cai, Yingqi; Zhai, Zhiyang; Shanklin, John (Frontiers in Plant Science, 2024)
The sensor kinase Sucrose Non-fermenting-1-Related Kinase 1 (SnRK1) plays a central role in energy and metabolic homeostasis. KIN10 is a major catalytic (α) kinase subunit of SnRK1 regulated by transcription, posttranslational modification, targeted protein degradation, and its subcellular localization. Geminivirus Rep Interacting Kinase 1 and 2 (GRIK1 and 2) are immediate upstream kinases of KIN10. In the transient protein expression assays carried out in Nicotiana benthamiana (N. benthamiana) leaves, GRIK1 not only phosphorylates KIN10 but also simultaneously initiates its degradation. Posttranslational GRIK-mediated KIN10 degradation is dependent on both GRIK kinase activity and phosphorylation of the KIN10 T-loop. KIN10 proteins are significantly enriched in the grik1-1 grik2-1 double mutant, consistent with the transient assays in N. benthamiana. Interestingly. Among the enriched KIN10 proteins from grik1-1 grik2-1, is a longer isoform, putatively derived by alternative splicing which is barely detectable in wild-type plants. The reduced stability of KIN10 upon phosphorylation and activation by GRIK represents a mechanism that enables the KIN10 activity to be rapidly reduced when the levels of intracellular sugar/energy are restored to their set point, representing an important homeostatic control that prevents a metabolic overreaction to low-sugar conditions. Since GRIKs are activating kinases of KIN10, KIN10s in the grik1 grik2 double null mutant background remain un-phosphorylated, with only their basal level of activity, are more stable, and therefore increase in abundance, which also explains the longer isoform KIN10L which is a minor isoform in wild type is clearly detected in the grik1 grik2 double mutant.